Examining primary school teachers' coping styles with stress according to different variables - Kilinç, Ali Çağatay; Recepoğlu, Ergün; Koşar, Serkan (SynthesisHub Advance Scientific Research, 2015)
The study seeks to explore primary school teachers' coping styles with stress according to such different variables as gender, branch, age, and total teaching experience. A total of 368 teachers employed in 14 primary schools in Ankara participated in the study. "Scale of Coping with Stress" was used to gather data. Independent samples t-test and one-way ANOVA were performed to analyze the data. The results revealed that teachers used self-confident and optimistic coping styles more than others. Results also indicated that teachers' perceptions of coping styles differed significantly on self-confident subscale according to gender variable and that their perceptions differed significantly on optimistic coping style according to both age and total teaching experience variables.
Keywords: Primary school; teacher; coping with stress; demographic variable; İlköğretim kurumu; öğretmen; stresle başa çıkma; demografik değişken; 4. Education; 7. Clean energy